Improvement of electricity reliability on the 330 kV Nigeria transmission network with static synchronous compensators - Omeje, Luke Uwakwe; Ohanu, Chibuike Peter; Anyaka, Boniface Onyemaechi; Sutikno, Tole (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The increasing demand for power has caused distortions in Nigeria’s 330 kV transmission network. This is a result of the bulk of the lines being heavily loaded at the moment, which leads to voltage drops and inconsistent electrical delivery. To ensure system reliability, it is therefore crucial to make sure that the system maintains a constant state under specific conditions. This research presents the use of static synchronous compensators (STATCOM) in the Nigerian 330 kV transmission network to reduce power loss and improve the voltage profile. To solve the problem of insufficient voltage and power losses, a three-phase network is simulated using the MATLAB/Simulink software. A three-level, 48- pulse STATCOM was employed to rectify the problem after weak buses were identified through load flow analysis. A 48- pulse converter that handled the STATCOM was used to control harmonic distortions in the system. The outcomes show how crucial the reactive power control mechanism is for regulating the system’s harmonics. However, the method was able to achieve real and reactive power losses of 12.5%. The STATCOM’s 3-level 48- pulse converter also resulted in a total 4.64% reduction in total harmonic distortion (THD).